Unraveling Vitiligo: From Immune Mechanisms to Promising Therapeutic Strategies - Artur Kovenskiy; Nurlubek Katkenov; Zhussipbek Mukatayev; Almagul Kushugulova (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Vitiligo is a dermatological condition affecting 1% of the global population, characterized by the loss of skin pigmentation. It appears in two main forms: nonsegmental (symmetrical depigmentation) and segmental (localized depigmentation). Oxidative stress and mitochondrial dysfunction in melanocytes cause vitiligo, while immune privilege protects hair follicle melanocytes, allowing for possible repigmentation. Genetic factors and associations with other autoimmune diseases, such as type 1 diabetes and thyroiditis, suggest a heritable autoimmune component. CD8+ T cells play a crucial role in vitiligo, targeting melanocytes and promoting apoptosis. These cells, along with IFN-γ signaling, contribute to disease progression. Therapies targeting these pathways, such as JAK inhibitors, have shown promise in repigmentation, particularly when combined with narrowband UVB phototherapy, a gold standard treatment. Surgical interventions, including punch grafting and suction blister grafting, show high efficiency but bring high risks of skin damage and hyperpigmentation. Vitiligo patients experience significant emotional suffering, requiring both a psychological and medical treatment approach. Dietary interventions, specifically those rich in antioxidants, may support disease treatment. Vitamin D, in particular, is a promising therapeutic agent by protecting melanocytes from oxidative stress via the WNT/β-catenin pathway. This review points out the need for more research on targeted therapies that combine immune regulation, phototherapy, and dietary strategies for effective vitiligo treatment.